Strategi Guru Pendidikan Agama Islam dalam Meningkatkan Karakter Positif Siswa - Suchi Nurul Khofifah; Ikhwan Ciptadi; Candra Wijaya (Transformasi Manageria Journal of Islamic Education Management, 2025)
The visible character of students has not been applied well in the school environment, the characteristics of students are very important to form a good personality. The purpose of this study was to determine the importance of the role of teachers in developing the character of students in elementary schools through child-friendly education. This research method uses a descriptive and qualitative approach, namely to describe, elaborate, and describe the efforts of teachers in developing the characteristics of students with data collection techniques, observation, and interviews. The results of the study indicate that teachers are good at understanding the characters that must be applied to students, the role of teachers is very important in developing the character of students through learning activities, habits, school culture, extracurricular activities and the school's vision and mission.